PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN TEKNIK PROBING-PROMPTING TERHADAP AKTIVITAS DAN HASIL BELAJAR FISIKA DI SMA - Siscawati Rizki Lasmo; Singgih Bektiarso; Alex Harijanto (FKIP Universitas Jember, 2017)
This research concentrated of guided inquiry model accompanied with probing-prompting technique for activity and learning outcomes physisics in SMA. The purposes of this research were to study the effect of using inquiry model accompanied with probing-prompting technique to student’s learning activities and kognitif student’s achievement. The type of this research was an experimental research by post-test control group design. Population of the research was all student’s at SMAN 1 Pakusari. The technique to collect data was documentation, observation, interview, and tests. The analysis result description of student learning activities for experiment class equals to 85.80 % is in active criteria. The analysis data of kognitif student’s achievement by using independent sample t-test for significant value (1-tailed) was 0,018(≤0,05), it’s mean the kognitif students’ achievement for experiment class is better than control class (Ha accepted and Ho refused). Conclusion of this research are : (1) student’s learning activities using guided inquiry model accompanied with probing-prompting technique is in active criteria which percentage level of activity is 85.80%. (2) Guided Inquiry Model accompanied with probing-prompting technique has significant effect of learning outcomes physisics in SMA. Keywords: guided inquiry model, probing-prompting technique